Portal e-Brosur Berbasis Modern Advertising Methods Untuk Efektifitas Periklanan - Erlangga Erlangga; Alfan Furqon (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2014)
Brochure printing is one of the marketing strategy for the company for marketing its products. Emarketing, advertising services are now getting the attention of the public since the aspects of information becomes important in business. Effective advertising activities deemed capable of affecting the Internet user community. By using modern advertising methods or modern advertising methods are expected E-brochures can be a new innovation to the world of e-marketing. Using this method there is Profit and loss of both marketers and consumers in particular. Advantages era could now access modern advertising we find easily on the internet so marketers can easily advertise their products but some rogue marketers who make fraudulent internet as a place to advertise that do not conform to the norms of moral, cultural and religious, and it can annoy even harm consumers or internet users. Based on the above background, the authors are interested in conducting research on building systems based Portal E-brochure Modern Advertising Methods For advertising effectiveness of e-marketing and pour in the form of a research proposal titled "Portal-Based E-Brochure Modern Advertising Methods For Effectiveness Advertising ".